2008
DOI: 10.1097/01.ogx.0000314816.42514.f5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insurance Status and Ethnicity With Cancer Stage at Diagnosis for 12 Cancer Sites: A Retrospective Analysis

Abstract: Persons living in the United States who lack private medical insurance are less likely to have access to medical care and to take part in cancer screening programs. Regional studies suggest that uninsured and Medicaid-insured individuals are likelier than those who are privately insured to present with advanced-stage cancer, but this has not been confirmed using contemporary national-level information. Complicating the problem is the observation that cancer patients from ethnic minorities are likelier than non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 0 publications
6
106
2
1
Order By: Relevance
“…The generalizability of the NCDB stage and insurance analyses also may be limited to patients who are seen at CoC-accredited facilities, which are more likely to be in urban areas and larger in size than non-CoC facilities. 35 There has been no formal validation of insurance status in the NCDB, which is another potential limitation that has been described elsewhere 36 ; however, it is the only national registry with insurance data. In addition, trends in increasing disparities should be interpreted cautiously, because the CIs overlapped for non-Hispanic whites and non-Hispanic blacks across the various periods.…”
Section: Discussionmentioning
confidence: 99%
“…The generalizability of the NCDB stage and insurance analyses also may be limited to patients who are seen at CoC-accredited facilities, which are more likely to be in urban areas and larger in size than non-CoC facilities. 35 There has been no formal validation of insurance status in the NCDB, which is another potential limitation that has been described elsewhere 36 ; however, it is the only national registry with insurance data. In addition, trends in increasing disparities should be interpreted cautiously, because the CIs overlapped for non-Hispanic whites and non-Hispanic blacks across the various periods.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with their nonHispanic white counterparts, Hispanic women are less likely to have received a screening mammogram within the past year, are more likely to be diagnosed with breast cancer at a later stage, experience a longer time from diagnosis to treatment, have greater disruptions in breast cancer treatment, and have a higher mortality rate from the disease. [3][4][5][6] Lynch syndrome, the most common hereditary colon cancer predisposition, accounts for 2%-4% of colorectal cancer. 7 It is recommended that individuals with Lynch syndrome or a family history of colorectal cancer increase the frequency of their screening colonoscopy and start screening at an earlier age.…”
mentioning
confidence: 99%
“…These pre-treatment factors then affect treatment allocation. It has been documented that out of 12 cancer sites, ovary has the largest amount of uninsured patients [8]. Several studies have demonstrated that African-Americans and Hispanics are more likely to present in advanced stages in various cancers including ovarian.…”
Section: Discussionmentioning
confidence: 99%
“…Because mortality rate has remained unchanged across all ethnicities throughout this time period, the representation of non-White ethnicities in the ovarian cancer population is likely on the rise [7]. Recent studies have also documented a larger proportion of non-White women presenting with advanced stage ovarian cancer in 75% of the total U.S. cancer population [8]. Furthermore, race, income and age have been associated with substandard treatment choices for ovarian cancer [9].…”
Section: Introductionmentioning
confidence: 99%